Der f 35: An MD‐2‐like house dust mite allergen that cross‐reacts with Der f 2 and Pso o 2. Issue 11 (23rd May 2017) - Fujimura, T.; Aki, T.; Isobe, T.; Matsuoka, A.; Hayashi, T.; Ono, K.; Kawamoto, S.
Abstract: Background: Dermatophagoides farinae is a source of airborne house dust mite (HDM) allergens. We elucidated IgE‐reactive allergens from D. farinae by two‐dimensional immunoblotting‐based allergenome analysis, and identified one new allergen, named Der f 35, that possesses IgE‐binding capacity comparable to that of Der f 2. The aim of this study was to clarify the allergenic capacity of new HDM allergen Der f 35. Methods: We cloned der f 35 from D. farinae mRNA and produced recombinant Der f 35 in Escherichia coli . The IgE‐binding capacity of Der f 35 and its cross‐reactivity with group 2 allergens from D. farinae and Psoroptes ovis were determined by enzyme‐linked immunosorbent assay (ELISA) and ELISA inhibition assays, respectively. Results: The deduced amino acid sequence for der f 35, which possesses the MD‐2‐related lipid‐recognition domain, showed higher identity with group 2 allergens from P. ovis (61.5%) and Blomia tropicalis (50.7%) than with Der f 2 (40.8%). Der f 35 showed IgE‐binding frequencies of 77.5% (31/40) for the native form upon allergenome analysis and 51.4% (18/35) for recombinant structure by ELISA. Der f 35 showed cross‐reactivity with Der f 2 and Pso o 2 in reaction with HDM‐allergic patients' IgE by ELISA inhibition assay. Conclusion: Der f 35 is a candidate major allergen from D. farinae, which is more similar to group 2 allergens from sheep scab mite and storage mites. Der f 35 could be responsible for the cross‐reactivity among group 2 mite allergens.